Effectiveness of lumbopelvic stabilization exercise education in patients with chronic mechanical low back pain [Kronik mekanik bel aǧrili hastalarda lumbopelvik stabilizasyon egzersiz eǧitiminin etkinliǧi] - (:unkn) unknown (My University, 2003)
Chronic low back pain is due to mechanical reasons in the majority of the cases. In recent years, exercise programs aimed to increase muscle control are preferred, rather than programs for strengthening isolated muscles around low back region. We investigated the efficacy of lumbopelvic stabilization exercises in comparison with conventional strengthening exercises of the abdominal and low-back muscles in patients with chronic mechanical low back pain. Thirty patients with chronic mechanical low back pain were enrolled and recruited into two groups. For 6 weeks, the first group received lumbovelvic stabilization exercise program, whereas the second group was given conventional program including isometric-isotonic exercises for abdominal and low back musculature. Both groups were given the same additional superficial, deep heat and analgesic electrotherapy modalities. Clinical efficacy was evaluated by assessing at the baseline, 2nd, 4th, 6th, and 8th weeks of treatment by isometric stability, visual analogue scale (VAS) for pain, manual muscle testing, range of motion measurements, Rolland-Morris Functional Activities Evaluation Test, and Oswestry Disability Evaluation Test. Both groups had significant improvements in themselves in relation to isometric stability test, range of motion, and manual muscle strength. However, the differences between the two groups were not significant. After 8 weeks of treatment, the first group had better VAS scores, Oswestry scores, and Rolland Morris functional evaluation scores than the 2nd group. Both exercises were found effective in the treatment of chronic low back pain. However, lumbopelvie stabilization exercises seemed to be more beneficial than standard strengthening exercises on pain reduction and functional parameters.
Keywords: Chronic low back pain; Exercise; Low back pain; Lumbopelvic stabilization exercises; Mechanical low back pain; Physical therapy